Particle breakage criteria in discrete-element modelling - de Bono, John P.; McDowell, Glenn R. (Thomas Telford ICE Publishing, 2016)
Previous work by the authors, using the discrete element method (DEM) has used the octahedral shear stress within a sphere together with a Weibull distribution of strengths and a size effect on average strength, to determine whether fracture occurs or not. This leads to fractal particle size distributions and a normal compression line which are consistent with experimental data. However there is no agreement in the literature as to what the fracture criterion should be and as yet it is not clear whether other criteria could lead to the correct evolution of voids ratio and particle size distribution under increasing stress. Various possibilities for the criterion have been studied in detail here to ascertain whether these other criteria may give the correct behaviour under normal compression. The use of the major principal stress within a particle, the mean stress, and the stress calculated from the maximum contact force on a particle are each investigated as alternatives to the octahedral shear stress. Only the criterion based on the maximum contact force is shown to give behaviour observed experimentally and the simulations shed further insight into the micro mechanics of normal compression.